Extended hemangioma from pharynx to esophagus that could be misdiagnosed as an esophageal varix on endoscopy. Issue 6 (6th December 2012) - Won, Jong Won; Lee, Hyun Woong; Yoon, Kyu Hyun; Yang, Suh Yoon; Moon, In Seok; Lee, Tae Jin
Abstract : Giant hemangioma in the neck and head is an uncommon vascular neoplasm and has an unpredictable clinical behavior. We report a hemangioma that extended from the pharynx to the esophagus that could have been misdiagnosed as an esophageal varix. A 42‐year‐old man with dilated varices‐like vessels on his esophagus that were incidentally detected by endoscopy was referred to our hospital for further evaluation. On re‐examined endoscopy, multiple vascular dilatations were noted in the pharynx, expanding into the esophagogastric junction. These dilatations looked like esophageal varices that are found in patients with liver cirrhosis. There was no significant abnormality, including liver cirrhosis, on the abdomino‐pelvic computed tomography scan. On the endoscopic esophageal biopsy, dilatedsubmucosal blood vessels were diagnosed as hemangioma. In consultation with an otorhinolaryngologist for evaluation of the risk of hemangioma, it was determined that the hemangioma was not dangerous to the patient as long as it did not cause hoarseness, dyspnea or dysphagia. We planned regular 6‐month follow ups. We report a case of extended hemangioma that could possibly have been misdiagnosed as an esophageal varix on endoscopy. Even if head and neck hemangioma is uncommon, careful consideration during endoscopy is required to avoid the misdiagnosis of varices or hemangioma.